2008
DOI: 10.3399/bjgp08x319666
|View full text |Cite
|
Sign up to set email alerts
|

Maximising recruitment and retention of general practices in clinical trials: a case study

Abstract: Three factors appeared important in recruiting practices: research topic, invitation method, and interest in research. Three factors appeared important in retaining practices: good communication, easy data-collection methods, and payment upon meeting pre-agreed targets. The effectiveness of these factors at facilitating recruitment and retention requires assessment in experimental studies. Keywords

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
56
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(61 citation statements)
references
References 16 publications
5
56
0
Order By: Relevance
“…The participating practices did not differ from non-participating practices in list size, number of GPs, social deprivation, or minority ethnic group composition of the practice population. 16 A nominated person consented on behalf of the whole practice for two participants to complete recorded interviews One lead GP from each of the intervention practices completed an interview directly after their practice had finished their involvement with the SHIFT trial (n = 17). Each lead GP was asked to identify a second informant for interview within the practice who was involved with the screening programme.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The participating practices did not differ from non-participating practices in list size, number of GPs, social deprivation, or minority ethnic group composition of the practice population. 16 A nominated person consented on behalf of the whole practice for two participants to complete recorded interviews One lead GP from each of the intervention practices completed an interview directly after their practice had finished their involvement with the SHIFT trial (n = 17). Each lead GP was asked to identify a second informant for interview within the practice who was involved with the screening programme.…”
Section: Methodsmentioning
confidence: 99%
“…The two PCTs are ranked among the most deprived in England (6th and 13th out of 354 boroughs) and have about 40% of their total populations from minority ethnic groups. 16 A universal screening policy was operating during the data collection period; that is, antenatal SC&T screening was offered to all pregnant women regardless of their ethnicity or family origin. 1 Of 119 eligible practices, 29 expressed an interest in participation.…”
Section: Methodsmentioning
confidence: 99%
“…73 Most of the studies in the review by Ross et al 73 were quantitative and the articles we identified in this subcategory were building on this evidence base. Rather than attempting to identify barriers as in the review by Ross et al, 73 they focused on strategies for overcoming the barriers, 78 filling gaps in the knowledge base such as barriers to recruiting health professionals rather than patients, 79 focusing on retention as well as recruitment, 77,79 considering barriers in new research environments 80 and considering barriers faced by different types of recruiters. 81 Most of the articles included here undertook the qualitative research to help recruitment in future trials.…”
mentioning
confidence: 99%
“…The literature suggests the relevance of a research question is an important motivator to participate in particular projects [8,15,16,22,23,28,[32][33][34][35]. Our finding that the FPs were giving comprehensive care to depressed patients suggests a commitment to the topic.…”
Section: Recruitment Of Physiciansmentioning
confidence: 70%